Trypophobia: an investigation of clinical features - Vlok-Barnard,Michelle (2017)
Objective: Trypophobia refers to the fear of, or aversion to, clusters of holes. We assessed clinical features of trypophobia and investigated whether it most resembled a specific phobia or obsessive-compulsive disorder. Methods: An online survey was conducted to gather information on sociodemographic variables, course and duration, severity, associated features, comorbid psychiatric diagnoses, and levels of psychological distress and impairment in individuals with trypophobia. The survey also explored whether such individuals experienced more fear or disgust, and whether symptoms showed more resemblance to a specific phobia or to obsessive-compulsive disorder. Associations of symptom severity and duration with degree of impairment were investigated. Results: One hundred and ninety-five individuals completed the questionnaire. Symptoms were chronic and persistent. The most common associated comorbidities were major depressive disorder and generalized anxiety disorder. Trypophobia was associated with significant psychological distress and impairment. The majority of individuals experienced disgust rather than fear when confronted with clusters of holes, but were more likely to meet DSM-5 criteria for specific phobia than for obsessive-compulsive disorder. Symptom severity and duration were associated with functional impairment. Conclusions: Given that individuals with trypophobia suffer clinically significant morbidity and comorbidity, this condition deserves further attention from clinicians and researchers.